A 33-Year-Old Man with Gynaecomastia and Galactorrhea as the First Symptoms of Graves Hyperthyroidism. (1st December 2016) - Khoohaphatthanakul, Somdul; Sriwijitkamol, Apiradee
Abstract : Graves' hyperthyroidism has a various number of well-recognized manifestations. Galactorrhea is a rare manifestation in this disease. We describe a 33-year-old man who presented with the symptoms of hyperthyroidism, gynaecomastia, and galactorrhea for 2 months. Physical examination revealed goitre, gynaecomastia, and galactorrhea, bilaterally. Laboratory investigations demonstrated high free thyroxine with suppressed thyroid-stimulating hormone level together with elevated anti-TSH receptor; therefore, the diagnosis of Graves' disease was confirmed. Other investigations to elucidate the etiology of galactorrhea were normal, so the galactorrhea was hypothesized to be caused by Graves' disease. The gynaecomastia and galactorrhea resolved with the successful treatment of hyperthyroidism. Although the galactorrhea is extremely rare in thyrotoxicosis male patients, to the best of our knowledge, this is the third case which reported gynaecomastia and galactorrhea in male patient who presented with thyrotoxicosis.